ACTIVITY-COMPETENCE APPROACH TO EDUCATION OF FUTURE ENGINEERS - Ponikarovska, S.; Поникаровская, С. В.; Понікаровська, С. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The essence of the activity-competence approach to higher education is dealt with, which promotes formation of essential for professional activity qualities, knowledges and skills, helping to fulfil professional duties in the chosen area.
ДЕЯТЕЛЬНОСТНО-КОМПЕТЕНТНОСТНЫЙ ПОДХОД К ОБРАЗОВАНИЮ БУДУЩИХ ИНЖЕНЕРОВ
ДІЯЛЬНІСНО-КОМПЕТЕНТНІСНИЙ ПІДХІД ДО ОСВІТИ МАЙБУТНІХ ІНЖЕНЕРІВ
Keywords: activity; approach; competence; skills; personalty; деятельность; подход; компетентность; навыки; личность; діяльність; підхід; компетентність; навики; особистість; 378.147